First record of the plant bug genus Euchilofulvius from Myanmar (Hemiptera: Heteroptera: Miridae: Cylapinae), with description of a new species - Yasunaga, Tomohide; Soe, Zayar; Naing, Shine Shane; Wolski, Andrzej (Zootaxa, 2015)
The cylapine plant bug genus Euchilofulvius was proposed by Poppius (1909) to accommodate a single Indonesian species, E. tibialis Poppius from Mentawai Islands. Several subsequent works have fragmentally added six valid species (Gorczyca, 2006, 2008; Poppius, 1913; Schuh, 1995, 2002–2014 online catalog; Yasunaga & Miyamoto, 2006; Yasunaga et al., 2012), and currently, the following seven members are known mainly from the Oriental Region: E. antennatus Gorczyca, 1999 (Sulawesi); E. carinatus (Poppius, 1913) (India, Sri Lanka); E. josifovi Gorczyca, 2008 (Malaya); E. lepidopterus Yasunaga & Miyamoto, 2012 (Okinawa, Japan); E. pallescens Gorczyca, 2002 (Solomon Islands); E. tibialis Poppius, 1909 (Indonesia, Malaysia, Thailand); and E. zdzislawi Gorczyca, 1998 (Sumatra).